Investigating topics, audio representations and attention for multimodal scene-aware dialog. (November 2020) - Kumar, Shachi H.; Okur, Eda; Sahay, Saurav; Huang, Jonathan; Nachman, Lama
Highlights: Present various architectural extensions to DSTC7 AVSD track baseline. Topics can be used to represent context of a dialog - improves performance. Exploration of multiple attention mechanisms during response generation. End-to-end audio classification convnet called AclNet improves performance. Abstract: With the recent advancements in Artificial Intelligence(AI), Intelligent Virtual Assistants (IVA) such as Alexa and Google Home have become a ubiquitous part of every home. Currently, such IVAs are mostly audio-based, but going forward, we are witnessing a confluence of vision, speech and dialog system technologies that are enabling the IVAs to learn audio-visual groundings of utterances. This will enable agents to have conversations with users about the objects, activities and events surrounding them. As part of the 7th Dialog System Technology Challenges (DSTC7), for Audio Visual Scene-Aware Dialog (AVSD) track, we explore three main techniques for multimodal dialog: 1) exploring 'topics' of the dialog as an important contextual feature for scene-aware conversations, 2) investigating several multimodal attention mechanisms during response generation and 3) incorporating an end-to-end audio classification sub network(AclNet) into our architecture. We present detailed analysis of our experiments and show that our model variations outperform the baseline system presented for this task.